An emerging – Social and emerging computing enabled philosophical paradigm for collaborative learning systems: Toward high effective next generation learning systems for the knowledge society. (October 2015) - Lytras, Miltiadis D.; Mathkour, Hassan I.; Abdalla, Hassan; Al-Halabi, Wadee; Yanez-Marquez, Cornelio; Siqueira, Sean Wolfgand Matsui
Abstract: The vast evolution of Social Computing in the last years and the tremendous improvement of novel technologies including cloud computing, open source technologies, recommender systems, personalized knowledge management systems, Big Data Systems, and Open Educational Resources approaches set a challenging context for the establishment of novel high effective approaches to Collaborative learning in both Business and Academia. This editorial provides an overview of a magnificent top quality research collection of articles related to the New Generation Collaborative Learning Systems. It is an opportunity for a scientific debate for the enabling technologies and the required adjustments in Academic Programs and Executives Training programs worldwide. It is a bold contribution to a new philosophical paradigm for the need to promote flexible, open, collaborative learning beyond time, personality, and place constraints. It seems that the old fashioned classroom based learning has to be enriched or in some cases replaced by technological learning innovations fostering collaboration between learners. Another important contribution of this special issue is the in depth discussion of a variety of requirements for next generation learning systems. This can be extremely useful for researchers interested on future research on the domain. Two more special issues on prestigious journals have been confirmed on similar topics for the next year in order to provide a continuity on this fascinating research domain that is directly linked to the vision of the Knowledge Society.